The Orphan G Protein-Coupled Receptor Gene GPR178 Is Evolutionary Conserved and Altered in Response to Acute Changes in Food Intake. - Vanni Caruso; Madeleine Le Grevés; Shahrzad Shirazi Fard; Tatjana Haitina; Pawel K Olszewski; Johan Alsiö; Helgi B Schiöth; Robert Fredriksson (PLoS ONE, 2015)
G protein-coupled receptors (GPCRs) are a class of integral membrane proteins mediating physiological functions fundamental for survival, including energy homeostasis. A few years ago, an amino acid sequence of a novel GPCR gene was identified and named GPR178. In this study, we provide new insights regarding the biological significance of Gpr178 protein, investigating its evolutionary history and tissue distribution as well as examining the relationship between its expression level and feeding status. Our phylogenetic analysis indicated that GPR178 is highly conserved among all animal species investigated, and that GPR178 is not a member of a protein family. Real-time PCR and in situ hybridization revealed wide expression of Gpr178 mRNA in both the brain and periphery, with high expression density in the hypothalamus and brainstem, areas involved in the regulation of food intake. Hence, changes in receptor expression were assessed following several feeding paradigms including starvation and overfeeding. Short-term starvation (12-48h) or food restriction resulted in upregulation of Gpr178 mRNA expression in the brainstem, hypothalamus and prefrontal cortex. Conversely, short-term (48h) exposure to sucrose or Intralipid solutions downregulated Gpr178 mRNA in the brainstem; long-term exposure (10 days) to a palatable high-fat and high-sugar diet resulted in a downregulation of Gpr178 in the amygdala but not in the hypothalamus. Our results indicate that hypothalamic Gpr178 gene expression is altered during acute exposure to starvation or acute exposure to palatable food. Changes in gene expression following palatable diet consumption suggest a possible involvement of Gpr178 in the complex mechanisms of feeding reward.